(Non)Financial Reporting (A)Symmetries in the Case of Amusement Parks in Europe - Daniela Artemisa Calu; Mădălina Dumitru; Mariana Elena Glăvan; Raluca Gina Gușe (Amfiteatru Economic)
Financial and non-financial reporting concerns in various industries are current challenges. With respect to tourism – the case of amusement parks – the existing research is scarce. In this context, the objectives of our research are the following: (i) to identify and critically analyse the key financial and non-financial reporting frameworks applicable in tourism, and respectively (ii) to identify the general trend and specific features of the financial and non-financial reporting of companies that manage major amusement parks in Europe. To achieve these objectives, we analysed the most recent sets of annual reports and other reports containing non-financial information, published by a number of five companies that hold the top 20 amusement parks in Europe. We followed a set of non-financial indicators that we selected based on the following reporting frameworks: Global Reporting Initiative (GRI), Sustainability Accounting Standards Board (SASB), European Federation of Financial Analysts (EFFAS), Organisation for Economic Co-operation and Development (OECD), European Tourism Indicators System (ETIS). The results obtained indicate the following existing trends: (i) in terms of financial reporting, there is symmetry for four of the 13 analysed aspects, others being reported differently and (ii) in terms of non-financial reporting, the degree of symmetry for the information disclosed is much lower that of financial reporting, only two of the 46 selected non-financial indicators (customer satisfaction and number of customers) being consistently reported by all the investigated companies.